Young children's Internet use at home and school: Patterns and Profiles - Johnson, Genevieve (SAGE, 2010)
Thirty-eight children in first and second grade completed a 10-item rating scale on Internet use at home and school. Results suggested that, in general, more children used the Internet at school than at home but home-based use was more often perceived as enjoyable. Three patterns of Internet use emerged suggesting three types of young users: home-based users demonstrated extensive, comprehensive, and enjoyable use of the Internet at home coupled with limited and less enjoyable Internet use at school; school-oriented information seekers reported mainly visiting websites, both at home and at school, but school access was preferred; and school-oriented communicators indicated primarily using email, both at home and at school, but school use was preferred. Implications for Internet literacy in young school children are discussed.